Applications of accessibility resources on informatics to low vision students - Marques, Lydia Cruz (2013)
The aim of this study was to verify the use of the accessibility options provided by the Windows-XP system with 12 students with low vision who attend an informatics course, with different diagnosis and visual impairments. The data collection was done by the assessment of visual acuity, visual field, sensitivity contrast and by observation of the performance in computer tasks. The results showed that for visual acuity equal or better of 0.2, the accessibility options accessed by the Accessibility Assistant were satisfactory. For visual acuity better than 0.1 and less of 0.2 it was necessary to increase the number of pixels for count. For visual acuity equal or less of 0.1, it was also necessary to be closer to the screen. It was concluded that the choice of accessibility resources for low vision is an individual task because of the diversity of visual impairments and that, the accessibility options of the Windows XP provided visibility in the proposed tasks.